A Feedback Loop Between Fatty Acid Metabolism and Epigenetics in Clear Cell Renal Carcinoma - Zhou Ye; Qi‐Xin Hu; Ming‐Liang Wei; Ji‐Dong Chen; Jia Shi; Ning‐Rong Yang; Lu Jiang; Jian Chen; Zhi‐Yuan Chen; Wei‐Min Yu; Yu Xiao; Kai‐Yu Qian; et al. (Advanced Science)
Abstract Lipid storage and epigenetic dysregulation are key features for clear cell renal carcinoma (ccRCC). However, the interplay between fatty acid metabolism and epigenetics in ccRCC remains to be further demonstrated. Here, the landscape of active enhancers is profiled in paired ccRCC samples and identifies 10171 gain variant enhancer loci (VELs) in the tumor tissues. Experimental validation reveals the enhancers targeting FABP5, FABP6, LPCAT1, MET, SEMA5B, SH3GL1, SNX33, and RHBDF2 are oncogenic. Further studies in organoids and animal models prove FABP5 as an oncogene. HIF‐2α and ZNF692 transcription factors regulate FABP5 expression through directly binding to its promoter and enhancer. FABP5 is essential for the lipid droplet formation driven by HIFs and critical for H3K27ac and enhancer activity in ccRCC cells. Thus, the study has identified potential targets for drug design and diagnosis and discovered the function of a feedback loop between epigenetics and lipid metabolism regulated by FABP5 in ccRCC.